Symbioses and Stress Joint Ventures in Biology - Seckbach, Joseph; Grube, Martin; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Symbioses and Stress centers on the question of how organisms in tight symbiotic associations cope with various types of abiotic and biotic stress. In its original sense, symbioses cover all kinds of interactions among unrelated organisms, whereas in a narrower concept, the term is often referred to as mutualism. Evolutionary biology recognizes symbiosis as an integrative process, and most fundamental evolutionary innovations arose from cooperative symbioses. Mutualisms contribute to stress tolerance, ecosystem stability, and evolutionary radiation of cooperating organisms. Modern eukaryotic cells are the result of the endosymbiotic union of prokaryotic ancestors as well as diverse exosymbiotic associations. This cooperative aggregation appears more successful than its independent parts. This new book presents functional and evolutionary aspects of mutually beneficial symbioses among unrelated organisms.
GENERAL INTRODUCTION -- On the Origin of Symbiosis -- Symbioses and Stress -- SYMBIOTIC ORIGIN OF EUKARYOTES -- Problems and Progress in Understanding the Origins of Mitochondria and Plastids -- The Origin of Eukarya as a Stress Response of Two-Membrane-Bounded Sexual Pre-karyote to an Aggressive Alphaproteobacterial Periplasmic Infection -- Low CO2 Stress: Glaucocystophytes May Have Found a Unique Solution -- AQUATIC SYMBIOSES -- Animal–Bacterial Endosymbioses of Gutless Tube-Dwelling Worms in Marine Sediments -- Multibiont Symbioses in the Coral Reef Ecosystem -- Cnidarian–Dinoflagellate Symbiosis-Mediated Adaptation to Environmental Perturbations -- Oxidative Stress-Mediated Development of Symbiosis in Green Paramecia -- Coral Symbiosis Under Stress -- Azolla as a Superorganism. Its Implication in Symbiotic Studies -- TERRESTRIAL SYMBIOSES -- Parasitism is a Strong Force Shaping the Fungus-Growing Ant–Microbe Symbiosis -- Evolution and Consequences of Nutrition-Based Symbioses in Insects: More than Food Stress -- Three in a Boat: Host-Plant, Insect Herbivore, and Fungal Entomopathogen -- Symbiotic Foraminifera and Stress -- Arbuscular Mycorrhizal Symbiosis Under Stress Conditions: Benefits and Costs -- Modulation of Aquaporin Genes by the Arbuscular Mycorrhizal Symbiosis in Relation to Osmotic Stress Tolerance -- How Rhizobia Survive in the Absence of a Legume Host, a Stressful World Indeed -- Life on a Leaf: Bacterial Epiphytes of a Salt-Excreting Desert Tree -- Physiological Responses to Stress in the Vibrionaceae -- The Stressed Life of Microbes in Plants -- Symbiotic Plant–Microbe Interactions: Stress Protection, Plant Growth Promotion, and Biocontrol by Stenotrophomonas -- Adaptation and Survival of Plants in High Stress Habitats via Fungal Endophyte Conferred Stress Tolerance -- Grass Endophyte-Mediated Plant Stress Tolerance: Alkaloids and Their Functions -- Endocytosis in Plant – Fungal Interactions -- Die Hard: Lichens -- Stress and Developmental Strategies in Lichens -- Green Algae and Fungi in Lichens: -- Green Biofilms on Tree Barks: More than Just Algae -- SYMBIOSES AND ASTROBIOLOGY -- Space Flight Effects on Lichen Ultrastructure and Physiology -- Resistance of Symbiotic Eukaryotes -- SUMMARY AND CONCLUSIONS -- Symbioses and Stress: Final comments.
Keywords: Microbiology; Evolutionary biology; Aquatic ecology .; Microbiology; Eukaryotic Microbiology; Evolutionary Biology; Freshwater & Marine Ecology